Variation of Suction during Wetting of Unsaturated Collapsible Gypseous Soils - A. H. Al-Obaidi, Ahmed; Y. Fattah, Mohammed; Kh. Al-Dorry, Mohammed (International Journal of Engineering and Technology, 2018)
Gypseous soils represent as essential soils that exhibit unsaturated behavior that differs completely than their behavior during soaking. Their strength, stiffness, and compressibility are dependent on the degree of saturation.The soil used in this research is disturbed natural gypseous soil having three different percentages of gypsum; 55, 30 and 18%. Nine model tests were conducted to investigate the variation of suction, settlement and total vertical stress with time, also, to study the effect of wetting on the volume change of unsaturated gypseous soil. The soil container used with inner dimensions of (length 700× width 700× height 600 mm). A square footing with (100 mm) sides was used. Models in loose, medium and dense soils were prepared. Watermark monitor data logger model 900M was used, with automatic data collection device that measures soil suction in kPa. The saturation process involved the complete saturation until the suction sensors readings approach to zero. The saturation process was established by allowing the water to infiltrate through the soil in upward-direction with a steady flow and head of 2 m.For all soil models, the time needed to reach the zero suction (saturation state) increased with the increase of the initial dry density. The initial value of suction for all soils increased with decreasing of the initial water content. The drop in the readings of suction may be due to the effect of gypsum content on the adsorption of water that leads to the saturation of the sensors surrounding area.